Stuck in the Wild—The Hydrology of the Teklanika River (Alaska) in the Summer of 1992 - Hill, David F.; Aragon, Christina (Frontiers in Earth Science, 2022)
In late spring of 1992, Christopher McCandless crossed the Teklanika River, west of Healy, Alaska (USA). His summer has been well documented both in the book and the movie `Into the Wild.' In early summer of 1992, he attempted to cross back over the river, but was stopped by high waters and he died later that summer. This paper investigates the hydrologic conditions of the Teklanika River watershed. We consider both climatological conditions and also conditions during the summer of 1992. We run process-based snowpack and runoff models in order to estimate the river hydrograph at the point of Mr.\ McCandless' attempted crossing. Our results demonstrate that the Teklanika river is very flashy during the summer, responding rapidly to strong episodic rainfall events. The main snowmelt signal occurred in mid-to-late May, after Mr. McCandless' first crossing and before his second attempt. The specific day of his attempted re-crossing corresponded to a large runoff event, driven by rainfall. We conclude that Mr.\ McCandless had unfortunate timing and that, had he tried to cross a day or two earlier or later, the outcome may have been different. This paper is also an opportunity to explore the hydrologic compromises that must be made when trying to study ungauged, or poorly gauged, areas. There is a spectrum of choices regarding input datasets and methodological simplifications and the correct location on that spectrum will depend on the particular watershed the objectives and expectations of the study.